Strategies to Improve Critical Thinking Skills for Children Through the Beyond Center and Circle Time (BCCT) Method - Faizatul Widat; Dewi Man Zilatul Hikmah; Zilviyatul Hasanah; Hasan Baharun (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to analyze and examine learning strategies in early childhood through the Beyond Center And Circle Time (BCCT) approach in improving critical thinking skills in early childhood. The subject of this research is RA Raudlatul Hasanah Condong Gading Probolinggo. This research uses a qualitative case study-type approach with observation, interview and documentation techniques. The data analysis is carried out circularly, starting with data display, reducing, and concluding. Sources of informants were obtained from school principals, teachers and guardians of students. The results of the study show that in improving critical thinking skills for early childhood at RA Raudlatul Hasanah by adopting the Beyond Center And Circle Time (BCCT) method, which is carried out in the following stages; first problem mapping, a second implementation of Beyond Centre And Circle Time (BCCT), third evaluation and follow-up plan. This research has implications that the BCCT method has a significant influence on improving thinking skills in early childhood, which can be seen when students ask questions, are enthusiastic about participating in teaching and learning activities and are always excited and cheerful in carrying out activities using this method.